2023
DOI: 10.1115/1.4056128
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Network Denoising Auto-Encoders for Intelligent Aircraft Engine Gas Path Health Signal Noise Filtering

Abstract: Removing noise from health signals is critical in gas path diagnostics of aircraft engines. An efficient noise filtering/denoising method should remove noise without using future data points, preserve important changes, and promote accurate diagnostics without time delay. Machine Learning (ML)-based methods are promising for high fidelity, accuracy, and computational efficiency under the motivation of Intelligent Engines. However, previous ML-based denoising methods are rarely applied in actual engineering pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…103 A CNN based denoising autoencoder technique showed significant efficiency in noise removal. 104 Zhifang et al 41 showed a sparse reconstruction using domain transfer technique to eliminate noise resulting in increased gas sensor performance.…”
Section: Gas Sensor Data Analysismentioning
confidence: 99%
“…103 A CNN based denoising autoencoder technique showed significant efficiency in noise removal. 104 Zhifang et al 41 showed a sparse reconstruction using domain transfer technique to eliminate noise resulting in increased gas sensor performance.…”
Section: Gas Sensor Data Analysismentioning
confidence: 99%
“…Deep learning has the potential to learn complex relationships and excel in extracting meaning information [1][2][3][4][5][6][7][8][9][10]. In paper [11], the author proposes the application of Convolutional Neural Network Denoising Auto-Encoders to intelligently filter noise in aircraft engine gas path health signals, enhancing signal quality for improved diagnostic accuracy. U-net is very popular network used in denoising, it includes the encoder and decoder that allows the network to learn important features of the signal.…”
Section: Introductionmentioning
confidence: 99%